2005
DOI: 10.2320/matertrans.46.329
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rust Layer Formed on Fe, Fe-Ni and Fe-Cr Alloys Exposed to Cl-Rich Environment by Cl and Fe K-Edge XANES Measurements

Abstract: Chloride in atmosphere considerably reduces the corrosion resistance of conventional weathering steel containing a small amount of Cr. Ni is an effective anticorrosive element for improving the corrosion resistance of steel in a Cl-rich environment. In order to clarify the structure of the protective rust layer of weathering steel, Cl and Fe K-edge X-ray absorption near edge structure (XANES) spectra of atmospheric corrosion products (rust) formed on Fe, Fe-Ni and Fe-Cr alloys exposed to Cl-rich atmosphere wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…Integrating (into Figure 8) the salinity data in Table 1 (Tables C1 and C2 This relationship confirms that it is possible for 1 g ZVM to remove >1 g NaCl [25]. This observation is consistent with a model of accretionary, polyionic, akaganeite/FeOOH nano rod formation where the bulk of the adsorbed NaCl is electrostatically bound in the hydration shells and the ionic layer surrounding each FeOOH, e.g., [22,23,25,78,79,[90][91][92][93][94][95][96][97][98][99][100]108].…”
Section: Impact Of Water Consumptionsupporting
confidence: 69%
See 1 more Smart Citation
“…Integrating (into Figure 8) the salinity data in Table 1 (Tables C1 and C2 This relationship confirms that it is possible for 1 g ZVM to remove >1 g NaCl [25]. This observation is consistent with a model of accretionary, polyionic, akaganeite/FeOOH nano rod formation where the bulk of the adsorbed NaCl is electrostatically bound in the hydration shells and the ionic layer surrounding each FeOOH, e.g., [22,23,25,78,79,[90][91][92][93][94][95][96][97][98][99][100]108].…”
Section: Impact Of Water Consumptionsupporting
confidence: 69%
“…Half reaction (Equation (38)) can result in a film of NaOH coating [201] the ZVI and a corrosion scale (Fe(OH)2, GR1, FeOOH) coating the ZVI [18, [68][69][70][71][72][73][74][75][76][77]87,88,93,94,96,[110][111][112]167,172,173,176,191,[202][203][204]. This model [150] results (as demonstrated in Section 4) in the amount of NaCl removed (and corrosion scale formed on the ZVI particles) being directly proportional to the inherent charge generated by ZVM TP/ZVM TPA, via the Nernst relationships [150], where [150]:…”
Section: Economic Implications Of Corrosion Scalementioning
confidence: 99%
“…Several researchers have studied the corrosion and corrosion mitigation of Fe-Ni alloys in different aggressive media [8][9][10]. They found that increasing the Ni content in the alloy improves its corrosion resistance [10].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Iron oxyhydroxides are also important corrosion products in various technologies. 10 Goethite (α-FeOOH) is the most thermodynamically stable form of iron at ambient conditions in the presence of water, and is the most abundant polymorph among iron oxyhydroxides. [11][12][13][14] Goethite redox properties have been the subject of intensive experimental research, especially in the context of redox-driven phase transformations to more reduced forms of Fe (e.g., ferrous iron), 15,16 surface speciation and redox transformations of metals, 9,17,18 reductive dissolution coupled to oxidative growth, and atom exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Akaganéite is also known to be the major component of corrosion products formed on Fe-steels exposed to the atmosphere. 10 Lepidocrocite was shown to play an important role in biogeochemical processes of Fe 2+ /Fe 3+ transformations. 23 Unlike goethite, however, redox properties of akaganéite and lepidocrocite have been experimentally explored to a much lesser extent.…”
Section: Introductionmentioning
confidence: 99%